Development of LC-HRMS methods for evaluation of metabolic conversion of 5-fluorocytosine at GDEPT procedure - Skvara, Pavel; Durinikova, Erika; Grabicová, Kateřina; Mordacikova, Erika; Matuskova, Miroslava; Vojs Stanova, Andrea (Journal of pharmaceutical and biomedical analysis, 2021)
Gene-directed enzyme/prodrug therapy represents one of the experimental treatment approaches. The system based on conversion of nontoxic prodrug 5-fluorocytosine to chemotherapeutic 5-fluorouracil by cytosine deaminase or fusion cytosine deaminase::uracil phosphoribosyl transferase belongs to the most frequently used. The detailed analysis of 5-fluorocytosine, 5-fluorouracil and its metabolites enables to understand various responses of tumour cells to treatment as well as mechanisms of resistance. A fast, sensitive and accurate methods based on liquid chromatography with high-resolution mass spectrometry (LC-HRMS) for the identification and quantification of 5-fluorocytosine, 5-fluorouracil and its major metabolites were developed. Two different hybrid high-resolution mass spectrometers sufficient for study of metabolic pathways were used. The LC-ESI IT-TOF MS method was successfully used for identification of 5-fluorocytosine, 5-fluorouracil and its metabolites in complex biological matrices (mesenchymal stromal cells and tumour cells media) and for confirmation of the metabolic conversion of 5-fluorocytosine even in chemoresistant tumour cells media samples. For quantification, the LC-HESI QExactive MS method was developed and validated. The developed method demonstrated a very good linear range for 5-fluorocytosine from 1 ng/mL to 1000 ng/mL and for its major metabolites from 5 ng/mL to 1000 ng/mL. The limits of detection and limits of quantification ranged from 1.1 to 26 ng/mL and from 3.6 to 87 ng/mL, respectively. Both developed methods confirmed the ability of gene-directed enzyme prodrug therapy to metabolically convert 5-fluorocytosine to 5-fluorouracil and its major metabolites in real samples of tumour cell media and mesenchymal stromal cells.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; flucytosin; Prodrugs; Chemotherapeutics; 5-fluorouracil; cytosindeaminasa; Metabolites; fluoruracil; Chromatography, Liquid; Fluorouracil; Flucytosine; chromatografie kapalinová; Cancer therapy; prekurzory léčiv; High resolution mass spectrometry; Cytosine Deaminase